Natural capitalism creating the next industrial revolution - Hawken, Paul; Lovins, Amory B.; Lovins, L. Hunter 1950- (Little, Brown, 1999)
"In the book, these durable, practical, and stunningly profitable principles are synthesized for the first time into the foundations for a system called natural capitalism."--BOOK JACKET
Keywords: Capitalisme - États-Unis - Prévision; Capitalismo - Estados Unidos - Predicciones; Pronóstico de la economía - Estados Unidos; Prévision économique - États-Unis; Siglo XXI - Predicciones; Vingt et unième siècle - Prévisions; Kapitalismus; Wirtschaftspolitik; Capitalism -- United States -- Forecasting; Economic forecasting -- United States; Twenty-first century -- Forecasts; Nachhaltigkeit; Prognose; Ökologische Marktwirtschaft; Estados Unidos - Política económica - 1993-2001; États-Unis - Politique économique - 1993-2001; USA; United States -- Economic policy -- 1993-2001